PENGARUH PENGGUNAAN ABU TULANG IKAN CAKALANG PADA PERKERASAN LENTUR - Metekohy, Juliet G; Buyang, Christy. Gery.; Tumalang, Levina (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Maluku Province, especially Ambon City, is the area with the largest capture fisheries sector in Indonesia. The amount of skipjack fish production from 2016 reached 1,742.00 tons and in 2020 skipjack fish production has increased to 4,493.46 tons (Ambon City fisheries office data). Large fish production but no management of skipjack fish bone waste, so it is not utilized by both the government and suasta. Skipjack fish bones have a good composition of bioavailability chemical content, the content contained in skipjack fish bones that have been extracted is moisture content 0.33%, ash 99.03%, protein 0.19%, fat 0.22%, and calcium content 83.25%, and phosphorus content 9.65%. Calcium in all samples is calcium phosphor apatite, apatite is a group of phosphorus minerals and calcium minerals that are generally present in rocks so that they can be applied to road building structures that use asphalt pavement. This study was conducted to determine the effect of using skipjack fish bone ash as a filler for asphalt mixture for AC-WC pavement. This is reviewed from the value of Marshall's stability with an experimental method. Some of the tests carried out are specific gravity testing, content weight, broken stone, sieve analysis, sand equivalent value, abrasion, material passing filter no.200 and marshall testing with reference to the specifications of Bina Marga 2018 Division 6. The test will be carried out by making 1 variation of skipjack fish bone ash filler of 3%. Keywords: Flexible Pavement, Compressive Strength, Fish Bone Ash,